2007
DOI: 10.1128/mcb.01993-06
|View full text |Cite
|
Sign up to set email alerts
|

CTCF Interacts with and Recruits the Largest Subunit of RNA Polymerase II to CTCF Target Sites Genome-Wide

Abstract: CTCF is a transcription factor with highly versatile functions ranging from gene activation and repression to the regulation of insulator function and imprinting. Although many of these functions rely on CTCF-DNA interactions, it is an emerging realization that CTCF-dependent molecular processes involve CTCF interactions with other proteins. In this study, we report the association of a subpopulation of CTCF with the RNA polymerase II (Pol II) protein complex. We identified the largest subunit of Pol II (LS Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 64 publications
(77 reference statements)
8
131
0
1
Order By: Relevance
“…In addition, CTCF was shown to interact directly with RNAPII (28). CTCF was shown to block enhancerand promoter-looping interactions (19,20) or to mark the boundary between active and inactive chromatin regions to establish chromatin domains and to insulate neighboring promoters from interfering with each other (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CTCF was shown to interact directly with RNAPII (28). CTCF was shown to block enhancerand promoter-looping interactions (19,20) or to mark the boundary between active and inactive chromatin regions to establish chromatin domains and to insulate neighboring promoters from interfering with each other (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…This initial generalized deregulation of gene transcription (animation) does not require de novo viral protein synthesis. How latent virus DNA quickly undergoes generalized transcriptional deregulation resulting in transcription of multiple immediate-early, early and late genes without prior protein or virus DNA synthesis is unknown, but may involve RNA polymerase II recruitment at CTCF/cohesin complexes (Chernukhin et al, 2007;Wada et al, 2009;Taslim et al, 2012). Interestingly, CTCF-directed cohesin rings can tether DNA strands present on different chromosomes for coordinated transcription (Kagey et al, 2010).…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VImentioning
confidence: 99%
“…3 Ctcf regulates chromatin architecture together with cohesion proteins, which are enriched at Ctcf-binding sites. [5][6][7] In addition, multiple functions of Ctcf are enabled by interaction with different binding partners like transcription factors (Yy1, Kaiso and YB-1), [8][9][10] chromatin modifying proteins (Sin3a, CHD8, Suz12), [11][12][13] RNA polymerase II 14 and poly(ADP-ribose) polymerase-1. 15 Recently, Ctcf was found to control MHC class II gene expression, 16 and it was reported that enforced overexpression of Ctcf in DC caused increased apoptosis, reduced proliferation and impaired differentiation.…”
Section: Introductionmentioning
confidence: 99%